AHP method in the analysis of the financial statements of companies in the metal-mechanical sector (Revista Brasileira de Contabilidade e Gestão, 2016)
The objective of this study is to create a ranking of steel and metal companies listed on the São Paulo Stock Exchange based on its financial performance and balance using the method of analytic hierarchical process (AHP). This research is characterized as descriptive, conducted through desk research, because the use of financial statements for data collection and quantitative approach for the application of AHP. We used indicators of liquidity, indebtedness, activity and profitability, derived from our consolidated financial statements obtained from the website of the Brazilian Securities Commission (CVM). Using these indicators, were established annual rankings and, from these, the general rankings for each group: liquidity, indebtedness, activity and profitability. It was found that the Tekno and Ferbasa companies occupy the top positions in liquidity indicators and debt, Mangels, Aços Villares and Usimimas occupy the top positions in activity and profitability indicators. The companies that had the highest degree of liquidity does not stand out with the highest degree of profitability and vice versa. After analyzing the general rankings was established a final ranking and it was found that the Tekno and Ferbasa that stood out in liquidity indicators and debt and had significant positions in profitability indicators, occupied the top positions.
Keywords: analysis of the financial statemenst; performance; AHP